A Review of Pain Assessment Methods in Laboratory Rodents - Turner, Patricia V (Comp Med, 2019)
Ensuring that laboratory rodent pain is well managed underpins the ethical acceptability of working with these animals in research. Appropriate treatment of pain in laboratory rodents requires accurate assessments of the presence or absence of pain to the extent possible. This can be challenging some situations because laboratory rodents are prey species that may show subtle signs of pain. Although a number of standard algesiometry assays have been used to assess evoked pain responses in rodents for many decades, these methods likely represent an oversimplification of pain assessment and many require animal handling during testing, which can result in stress-induced analgesia. More recent pain assessment methods, such as the use of ethograms, facial grimace scoring, burrowing, and nest-building, focus on evaluating changes in spontaneous behaviors or activities of rodents in their home environments. Many of these assessment methods are time-consuming to conduct. While many of these newer tests show promise for providing a more accurate assessment of pain, most require more study to determine their reliability and sensitivity across a broad range of experimental conditions, as well as between species and strains of animals. Regular observation of laboratory rodents before and after painful procedures with consistent use of 2 or more assessment methods is likely to improve pain detection and lead to improved treatment and care—a primary goal for improving overall animal welfare.